1990
DOI: 10.1037/0022-3514.59.5.981
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in effects of physical attractiveness on romantic attraction: A comparison across five research paradigms.

Abstract: Evolutionary and sociocultural theories of mate selection preferences contend that men place greater value on physical attractiveness than do women. Thus, meta-analyses were conducted of findings from 5 research paradigms that have examined the hypothesis: (a) questionnaire studies, (b) analyses of lonely hearts advertisments, (c) studies that correlate attractiveness with opposite-sex popularity, (d) studies that correlate attractiveness with liking by a dyadic interaction partner, and (e) experiments that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
283
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(320 citation statements)
references
References 69 publications
28
283
0
9
Order By: Relevance
“…r Alternatively, the one-sided gender bias hypothesis states that men, more than women, selectively attend to attractive members of the other sex. This hypothesis is consistent with research suggesting that men value physical attractiveness in potential mates relatively more than females do (Buss, 1989;Feingold, 1990Feingold, , 1992Kenrick et al, 1990). For example, women shown photos of physically attractive men did not alter their commitment to their partners, as men did when exposed to physically attractive women .…”
Section: Physical Attractiveness and The Eye Of The Beholdersupporting
confidence: 81%
See 2 more Smart Citations
“…r Alternatively, the one-sided gender bias hypothesis states that men, more than women, selectively attend to attractive members of the other sex. This hypothesis is consistent with research suggesting that men value physical attractiveness in potential mates relatively more than females do (Buss, 1989;Feingold, 1990Feingold, , 1992Kenrick et al, 1990). For example, women shown photos of physically attractive men did not alter their commitment to their partners, as men did when exposed to physically attractive women .…”
Section: Physical Attractiveness and The Eye Of The Beholdersupporting
confidence: 81%
“…Much evidence indicates that physical attractiveness often plays a major role in romantic relationships (e.g., Feingold, 1990Feingold, , 1992Shackelford, 2001;Simpson et al, 1990), and so we might expect people to direct their attention selectively to individuals who are physically attractive; this tendency should be exaggerated among those perceivers currently interested in romance. We explored this general idea in a series of five experiments, focusing specifically on several alternative hypotheses derived from evolutionary considerations (Maner et al, 2003).…”
Section: Physical Attractiveness and The Eye Of The Beholdermentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, humans in general tend to look for physically attractive mates. Research on preferences for partner characteristics shows that both men and women prefer attractive over unattractive partners (Feingold, 1990). Thus, physical attractiveness serves as an indicator to identify genetically viable mates (Thornhill & Gangestad, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that physical attractiveness is more closely related to self-esteem and a more important determinant of popularity with the opposite sex for females than for males (Feingold, 1990(Feingold, , 1992. However, as a caveat to this suggestion, other meta-analytic reviews (Eagly et al, 1991;Langlois et al, 2000) have not found support for the hypothesis that the physical attractiveness stereotype is stronger for females than for males.…”
Section: Models and Measurement Of The Physical Selfmentioning
confidence: 75%